Analysis of housing in the axes of accessibility and functionality of a housing unit designed for the elderly (Research, Society and Development, 2020)
Urban development and population aging are distinct, multiple and complex processes. Emphasizing the right to the city, the issue of housing stands out, in this sense, living in a dignified manner, conveys conditions in the preservation and identity of the resident, guaranteeing the place's belonging. Therefore, the general objective of this study is to analyze the habitability of a housing unit in a condominium designed for the elderly in the city of Patos-PB. To achieve this objective, it is necessary to specifically: assess accessibility through basic guidelines; analyze the functionality and usability of residents, and finally; subsidize improvements in the habitability of housing in new condominiums to be implemented, and thus contribute to the housing program under study. This research is characterized as exploratory and descriptive, as far as its nature is concerned, the field study was approached, where on-site visits and surveys of the project under study were carried out, through measurements, comparisons and observances of the resident's usability. It was observed that the initial proposal of the project meets the basic needs, with regard to the accessibility guidelines, however, when analyzing the habitability in the functionality axis, it is considered that the condominium was not properly designed for the elderly with regard to I respect the conditions that stimulate the elderly resident to experience the space in a more active and independent way.